Potential of Purslane (Portulaca oleracea L.) in Phytoremediation: A Study on the Bioaccumulation and Bio-Transfer of Cadmium, Nickel, and Copper in Contaminated Soils - Havva Aybike Erkoç; Bihter Çolak Esetlili (Journal of Agricultural Sciences)
As industrial and agricultural activities intensify and technology rapidly advances, soil pollution has escalated to alarming levels. The increasing contamination of agricultural areas and the crops cultivated therein has emerged as a significant contemporary issue. Phytoremediation, the use of plants to remove pollutants, is a promising method for mitigating soil heavy metal contamination. This study investigates the bioaccumulation capacity of purslane (Portulaca oleracea L.), a potential phytoremediator, in soils artificially contaminated with cadmium (Cd), nickel (Ni), and copper (Cu). The purslane was cultivated under controlled conditions with varying doses of Cd, Ni, and Cu. After 55 days, the plants were harvested and analysed for heavy metal concentrations in their roots, stems, and leaves. The results demonstrated a direct correlation between environmental heavy metal concentration and plant heavy metal content, with the most significant accumulation occurring in the roots. The leaf chlorophyll content was adversely affected by increased Cd, Ni, and Cu applications. The highest Cu, Ni, and Cd contents were found in the roots at 140 mg kg-1 Cu, 80 mg kg-1 Ni, and 20 mg kg-1 Cd applications, respectively. The bio-transfer coefficient (BTC), a measure of heavy metal transport from the root region to the leaves, was calculated. The BTC values ranged from 0.84-1.09 for Cu, 0.39-0.84 for Ni, and >1 for Cd at the Control and 5 mg Cd kg-1 treatments. These findings suggest that purslane has potential for phytoremediation of heavy metal-contaminated soils, although the bioaccumulation and bio-transfer of heavy metals are dependent on the specific metal and its concentration in the soil. The study also highlights the potential risks associated with the consumption of plants grown in heavy metal-contaminated soils, as heavy metals can accumulate in different plant tissues, potentially entering the food chain.